'He was wearing street clothes, not pyjamas': common mistakes in lawyers' assessment of legal capacity for vulnerable older clients. (2nd January 2018) - Barry, Lise
ABSTRACT: Lawyers are increasingly called upon to deal with older clients and have ethical responsibilities to attest to their capacity for legal decision-making. As witnesses to enduring documents, the making of wills and other significant advance planning transactions, lawyers play a role in preventing elder abuse and in upholding the rights of older people. To date however, there has been very little empirical research examining how lawyers assess an older person's legal decision-making capacity. This article presents research examining three years of capacity complaints made to the New South Wales Office of Legal Services Commissioner. Four case studies from the complaint files expose some common failings in the way that lawyers interact with older clients who have experienced cognitive impairment. The process of capacity assessment is viewed through the theoretical lens of vulnerability to highlight how the actions of lawyers and regulators can exacerbate the inherent and situational vulnerability of older people with a cognitive impairment. The author argues that improvements in capacity guidelines, legal education and robust enforcement of ethical rules are required to safeguard the rights of older clients and help prevent abuse. The findings will have implications for lawyers and regulators everywhere dealing with an ageing population.